URGENSI PUTUSAN BAWASLU DALAM PENYELESAIAN SENGKETA PROSES PEMILIHAN UMUM - Yusrizal Adi Syaputra, Muhammad (Grondwet, 2022)
This research aims to review and analyze Bawaslu's position in resolving disputes arising in the election process. In addition, this study is also haunted to find out the urgency of the Bawaslu verdict in resolving disputes over the election process. The research method used is normative juridical with a statutory approach. The data source obtained comes from secondary data using qualitative analysis. The first research result is the Election Supervisory Agency (Bawaslu) domiciled as an auxiliary state organ that has the main function of supervision of the holding of elections. Bawaslu in carrying out the judicial quasi process to resolve the election dispute. The object of Bawaslu's authority consists of the decision of the KPU where the decision in question is in the form of a Decree and or Event News.